Meningkatkan Kemampuan Operasi Hitung Bilangan Asli melalui Habituasi Penggunaan Aplikasi Test of Second Mathematics (TOSM) - Wahyudi, Rachmat Satrio; Ratnaningsih, Nani (Jurnal Penelitian dan Pembelajaran Matematika, 2025)
This study aims to improve the basic arithmetic skills of eighth-grade students through the habituation of using the Test of Second Mathematics (ToSM) application. The research method used is quantitative with a one-group pretest-posttest design. The research sample was eighth-grade students of SMPN 2 Cimerak in the 2024/2025 academic year. Data was collected through basic arithmetic skill tests before and after the habituation treatment. The collected data was analyzed using descriptive statistics. The results showed an improvement in students' basic arithmetic skills after the ToSM habituation. Based on the analysis using the average N-gain value, the improvement in addition, subtraction, multiplication, and division operations falls into the low category. This indicates that ToSM habituation can improve students' speed and accuracy in performing basic arithmetic operations. This study concludes that the habituation of using the ToSM application is an effective strategy for improving students' basic arithmetic skills. It is recommended that schools integrate the use of ToSM into mathematics learning to address the problem of low basic arithmetic skills among students.